PENEMPATAN DAN DISIPLIN KERJA PEGAWAI: PENGARUHNYA TERHADAP KINERJA PEGAWAI MELALUI SEMANGAT KERJA - Yusuf Riesata; Ranthy Pancasasti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Inappropriate work placement, lack of discipline and employee morale are factors that can affect employee performance. The purpose of this study was to analyze the effect of placement and work discipline on employee performance through work morale as an intervening variable. The object of this research is non-civil servant employee at RSUD dr. Drajat Prawiranegara with the number of samples taken as many as 98 employees. Analysis of research data using the SEM-PLS method which includes testing the outer model, inner model and hypothesis testing. Based on the results of data analysis, it is known that placement has a significant positive effect on employee morale and performance, while work discipline has no effect on employee morale or performance. The results of the mediation test show that morale is only an intervening between placement and employee performance